Solve for c 5(c+4)+2(2c-1)=-9

Math
5(c+4)+2(2c-1)=-9
Simplify 5(c+4)+2(2c-1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
5c+5⋅4+2(2c-1)=-9
Multiply 5 by 4.
5c+20+2(2c-1)=-9
Apply the distributive property.
5c+20+2(2c)+2⋅-1=-9
Multiply 2 by 2.
5c+20+4c+2⋅-1=-9
Multiply 2 by -1.
5c+20+4c-2=-9
5c+20+4c-2=-9
Simplify by adding terms.
Tap for more steps…
Add 5c and 4c.
9c+20-2=-9
Subtract 2 from 20.
9c+18=-9
9c+18=-9
9c+18=-9
Move all terms not containing c to the right side of the equation.
Tap for more steps…
Subtract 18 from both sides of the equation.
9c=-9-18
Subtract 18 from -9.
9c=-27
9c=-27
Divide each term by 9 and simplify.
Tap for more steps…
Divide each term in 9c=-27 by 9.
9c9=-279
Cancel the common factor of 9.
Tap for more steps…
Cancel the common factor.
9c9=-279
Divide c by 1.
c=-279
c=-279
Divide -27 by 9.
c=-3
c=-3
Solve for c 5(c+4)+2(2c-1)=-9

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top